Eksplorasi Etnomatematika Pada Keraton Ismahayana Landak Ditinjau Dari Konsep Geometri - Agustin, Handini Dwi; ., Halini; Mirza, Ade (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2024)
Keraton Ismahayana Landak is a Malay royal heritage palace located in Landak Regency. Ismahayana Landak Palace has architecture in the form of a typical West Kalimantan stilt house. This research originated from mathematics learning in schools that were less supportive in integrating local culture-based mathematics learning. In addition, some students still do not know the existence and history of Ismahayana Palace. The purpose of this study is to describe the concept of geometry and the philosophical meaning contained in the Ismahayana Palace of Landak. The research method used is descriptive method combined with ethnographic approach. Research data obtained from observation sheets, interview guidelines, and documentation. In this study, the object of research is Keraton Ismahayana Landak and the management of Keraton Ismahayana Landak and Malay figures as research subjects. The results showed that the Ismahayana Landak Palace has a geometry concept, namely flat and spatial shapes that contain philosophical meaning in it. The ethnomathematics activities contained in the Ismahayana Landak Palace are counting, locating, and explaining.